The Intersection of Race and Gender Among Black American Adolescents. Issue 1 (19th May 2018) - Seaton, Eleanor K.; Tyson, Karolyn
Abstract : This study employed an exploratory sequential mixed‐methods design to examine the intersection of race and gender among Black American adolescents, aged 11–19. The quantitative component ( n  = 344) used survey data to examine gender differences in peer‐perpetrated and adult‐perpetrated racial discrimination experiences, and no gender differences were evident. Qualitative data ( n  = 42) probed how males and females interpret discrimination experiences given the intersection of race and gender. Although the majority of participants believed that Black males and females have similar experiences, some believed that Black males face more racial discrimination. However, analyses revealed social disadvantages for Black females given that they report inappropriate comments and unwelcome hair touching and limited opportunities for interracial dating compared with Black males.